UN Convention on the Rights of the Child: Provision - Sadowska, Monika (International Children's Rights, 2024)
The study outlines the guarantees laid down in the CRC to secure the children’s right to have access to certain resources and services necessary for their proper growth and development, such as the right to healthcare and education, the right to benefit from social security, as well as the right to rest and leisure, which are commonly referred to as the ‘Provision Rights’. The complex nature of a child’s developmental needs implies that the realisation of these rights cannot occur in isolation from protecting the rights of the family. Parents bear the primary responsibility for the upbringing and development of the child, whereas the State’s responsibility is of a subsidiary nature, expressed primarily in measures to ensure that the child’s needs and all-round development, which parents are unable to provide, are fulfilled.Keywords: Provision Rights, child’s right to healthcare, child’s right to education, child’s right to social security